Sluice Gate Operation and Managed Water Levels Improve Predicted Estuarine Lake Water Quality - Kim, Semin (Salehan Institute of Higher Education, 2025)
Saemangeum Lake, an artificial estuarine lake, suffers from a pollutant load from an upstream watershed that is insufficiently mitigated by current load reduction measures. However, no studies have reported simulated flow direction and velocity for a lake. This study aimed to present an alternative solution based on managing water levels and sluice gate operation. Data were collected on water quality, sluice gate operation, water levels, tidal currents, and flow velocities. Next, the inflow and outflow volumes through the sluice gates were calculated. The Delft3D model was applied to predict water quality in a number of simulated scenarios. Finally, streamline and vorticity were calculated to evaluate hydraulic phenomena, while the ecology-based seawater quality index was employed to evaluate water quality. Analysis of flow characteristics revealed a large-scale clockwise vortex formed in the area where the Mangyeong River meets one of the sluice gates. It revealed a two-layer circulation with different flows in the surface and bottom layers. Evaluation of predicted water quality showed that one-way circulation, alternated in 15-day cycles, significantly improved major water quality items at most stations. Collectively, these findings demonstrate the effect that gate operation and managed water levels can have on the water quality of estuarine lakes. Doi: 10.28991/CEJ-2025-011-01-015 Full Text: PDF